A Novel Tool to Predict Postoperative Opioid Need after Laparoscopic Appendectomy in Children: A Step toward Evidence-Based Pain Management - Unglert, Ann-Katrin; Lehnick, Dirk; Szavay, Philipp O.; Zundel, Sabine (European Journal of Pediatric Surgery, 2022)
Background Optimizing postoperative pain treatment is essential to minimize morbidity, lower costs, and ensure patient and parent satisfaction. This study aims at identifying pre- and intraoperative parameters predicting opioid needs after laparoscopic appendectomy to enable timely and adequate postoperative pain control.Materials and Methods A retrospective analysis of patients treated with laparoscopic appendectomy for appendicitis between January 2018 and March 2019 was performed. Multiple logistic regression was applied to identify predictors of opioid demand.Results Based on our analysis, we developed a prediction tool for opioid requirements after laparoscopic appendectomies in children. The integrated parameters are: presence of turbid fluid, age, white-blood-cell count, symptom duration, and body temperature.Conclusion We developed an algorithm-based predictor tool that has the potential to better anticipate postoperative pain and, thereby, optimize pain management following laparoscopic appendectomies in children. The proposed predictor tool will need validation through further prospective studies.
Keywords: pain; opioids; appendectomy; pediatric surgery; child